Distribution of palytoxin in coral reef organisms living in close proximity to an aggregation of Palythoa tuberculosa. (1st March 2016) - Aratake, Satoe; Taira, Yosuke; Fujii, Takuma; Roy, Michael C.; Reimer, James D.; Yamazaki, Tomoko; Jenke-Kodama, Holger
Abstract: Palytoxin is a strong marine toxin that was first isolated from the zoantharian Palythoa toxica and later from other species of the genus Palythoa . How the toxin gets into the animal remains an unsolved question. To study the specificity of palytoxin distribution, the toxin content of Palythoa tuberculosa and other organisms living in close association on a coral reef in Okinawa were analysed by mass spectrometry. In contrast to earlier reports, palytoxin was only detected in P. tuberculosa colonies. Graphical abstract: Highlights: 64 Palythoa samples and 55 other marine specimens from Teniya, Okinawa, Japan were analysed by LC–MS. Extracts were screened for palytoxin (PTX) and congeners, but only PTX and 42-hydroxy PTX were found. PTX and 42-hydroxy PTX were exclusively found in the species Palythoa tuberculosa . PTX distribution was extremely specific at the Teniya sampling site.